(3hGajI aj TQM TGajIs - (3CMeO Hf eMeO Hf CHj HcQ Hf eMeOs ((3eMeO Hf YeQ GdgNdjs)
(3ChdgG (B:s
(3GdMeO ddg (B.. (3deG cGf ddCfGe aVd GdGJeGe HePGcQI cJGH TGajI CNJ cGajI ddEeGe (B..(3CHj YeQh YKeGf Hf GdMGLH (B.. (3CQOJ Cf CTQM dg TQMG hTQhMg hEf cKQJ hbYJ aj WQaj GdEjLGR GdeNd hGdEWfGH Gdeed (B...s
(3BNQgG (B:s
.. (3hHGdjGA CNQi dGMJeGdg Cj GMJeGd Cf jchf Cdag YOg GdhGh hGh GdMQha ade jcJH efgG HGdjGA ZjQ Hdi hPdc deLjA GdEeGdI ajg hZjQ Edi hYdi (B... (3GdMeO ddgs
(3JGQjN GdJCdja (B: 4 (3Ph GdMLI (B813 (3g`s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3GdUQas